"DENGUE IgG/IgM ANTIBODI RAPID TEST" (IR-113c) SEBAGAI PERANGKAT DIAGNOSTIK CEPAT DEMAM BERDARAH DENGUE - Utami, Basundari Sri; Tuti, Sekar; Novriani, Harli (Media Penelitian dan Pengembangan Kesehatan, 2008)
Dengue Haemorraghic Fever (DBD) remains one of the main major health problem. The morbidity rate increases from year to year, especially in the urban area like Jakarta. It is caused by flaviviridae virus, and transmitted through mosquitoes biting (Aedes aegypti or Aedes albopictus). Although the morbidity from 1990 to 2006 was high (total cases showed 22.807 in 1990, and 111.730 in 2006), the case fatality rate (CFR) were gradually decrease (CFR showed 3,60% in 1990 and 1,41% in 2006). The problem is in the early clinical manifestation of dengue virus infection causes a broad spectrum of illnesses, may as an asymptomatic infection, a like undifferentiated fever, a common influenza, a chikungunya, or as a typhoid fever. Prompt and accurate diagnosis is needed, to saving the lives of DBD patients. In order to get prompt and accurate diagnosis for dengue virus infection, we validated a Dengue IgG/IgM Antibody Rapid Test/IR-113c) (produced by Oncoprobe), using 61 sera taken from dengue infected patients from Jakarta, Semarang andMedan. All sera were paired or taken from acute and convalescence phases of infection. RDT result were compare to HI (Haemaglutination Inhibition) Test as a gold standard, ELISA test was also be done to measure the titers oflgM and IgG. It was found that this device showed 76,9% (76,8-77) sensitivity (Se), 77,7% (77,6-77,8) specivicity (Sp), 77,05% (76,95-77,15) accuracy, 95,2% (95,45-95,25) and 36,8% (36,68-36,92) positive predictive value (ppv) and negative predictive value (npv), all those result were statistically valid (x'=10,7, p = 0,001). The convalescence sera showed 98,1% (98,07-98,13) sensitivity (Se), 77,7% (77,6-77,8) specivicity (sp), 95,1% (95,05-95,15) accuracy, 96,2% (96,16-96,24) and 87,5% (87,42-87,58) positive predictive value (ppv) and negative predictive value (npv), all those result were statistically valid (x2 = 38,74, p = 0,000). Dengue IgG/IgM Antibody Rapid Test/IR-113c has an adequate sensitivity and accuracy however it is less specific. This device showed higher validity for convalence sera.